Early Protein Markers of Necrotizing Enterocolitis in Plasma of Preterm Pigs Exposed to Antibiotics - Jiang, Yan-Nan; Muk, Tik; Stensballe, Allan; Nguyen, Duc Ninh; Sangild, Per Torp; Jiang, Ping-Ping (Frontiers in Immunology, 2020)
Background: Most hospitalized preterm infants receive antibiotics in the first days of life to prevent or treat infections. Short-term, early antibiotic treatment may also prevent the microbiota-dependent gut inflammatory disorder, necrotizing enterocolitis (NEC). It remains a challenge to predict NEC, and a few early blood diagnostic markers exist. Using preterm pigs as model for infants, blood parameters and plasma proteins affected by early progression of NEC were profiled in preterm pigs subjected to oral, systemic, or no antibiotics after preterm birth. Methods: Preterm newborn pigs were treated with saline (CON) or antibiotics (ampicillin, gentamicin, and metronidazole) given enterally (ENT) or parenterally (PAR), and fed formula for 4 days to induce variable microbiome-dependent sensitivities to NEC. The gut was collected for macroscopic scoring of NEC lesions and blood for hematology, blood biochemistry, and LC/MS-based plasma proteomics. Statistical modeling was applied to detect plasma proteins affected by NEC and/or antibiotics. Results: Analyzed across different antibiotic regimens, NEC progression was associated with altered blood parameters and abundance of 89 plasma proteins that were functionally involved in extracellular membrane destruction, lipid metabolism, coagulopathy, and acute phase response. Large NEC-related changes were observed in abundance of RBP4, FGA, AHSG, C5, PTPRG, and A-1-antichymotrypsin 2, indicating potential serving as early markers of NEC. Conversely, antibiotic treatment, independent of NEC, affected only 4 proteins with main differences found between ENT and CON pigs. Conclusion: Early postnatal development of NEC lesions is associated with marked plasma protein changes that may be used for early NEC diagnosis.